2000
DOI: 10.1038/35018508
|View full text |Cite
|
Sign up to set email alerts
|

The 3.2-Å crystal structure of the human IgG1 Fc fragment–FcγRIII complex

Abstract: The immune response depends on the binding of opsonized antigens to cellular Fc receptors and the subsequent initiation of various cellular effector functions of the immune system. Here we describe the crystal structures of a soluble Fc gamma receptor (sFc gammaRIII, CD16), an Fc fragment from human IgG1 (hFc1) and their complex. In the 1:1 complex the receptor binds to the two halves of the Fc fragment in contact with residues of the C gamma2 domains and the hinge region. Upon complex formation the angle betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
625
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 680 publications
(663 citation statements)
references
References 46 publications
34
625
0
4
Order By: Relevance
“…In the purified monomeric deamidated sample, reduced binding was still measured on the low‐affinity Fcγ receptors, which could only be attributed to D‐N. The main deamidation site of this IgG is present in the CDR at the LC (up to 40% modified), which is positioned relatively far away from the Fc interaction site (lower hinge, upper CH2 domain 37, 38). Deamidation at this position is not likely to change the folding of the protein in such a way that it would have a large impact on Fc receptor binding.…”
Section: Discussionmentioning
confidence: 96%
“…In the purified monomeric deamidated sample, reduced binding was still measured on the low‐affinity Fcγ receptors, which could only be attributed to D‐N. The main deamidation site of this IgG is present in the CDR at the LC (up to 40% modified), which is positioned relatively far away from the Fc interaction site (lower hinge, upper CH2 domain 37, 38). Deamidation at this position is not likely to change the folding of the protein in such a way that it would have a large impact on Fc receptor binding.…”
Section: Discussionmentioning
confidence: 96%
“…The first crystal structure of FcγRIII-IgG1-Fc complex was reported in 2000 9 . The FcγRIII used in the study was a soluble FcγRIIIb (sFcγRIIIb) produced in E. coli and the Fc was isolated from pooled human IgG1.…”
Section: Molecular Mechanisms To Account For the Enhanced Affinity Ofmentioning
confidence: 99%
“…As the sFcγRIII preparation used in the study was unglycosylated, it was impossible to evaluate the impact of its N -linked glycan on the FcγRIII-Fc interaction. Nonetheless, the authors did highlight that Asn162 is a potential glycosylation site of FcγRIII that is close to a binding site and a larger carbohydrate moiety attached to this site may influence the affinity to IgG 9 . Indeed, a subsequent study revealed that, compared to the unglycosylated form of FcγRIII (by mutating Asn162 to Gln162), the glycosylated FcγRIII (Asn162) showed reduced affinity for native (fucosylated) IgG antibodies, while antibodies with or without the core fucose showed a similar affinity for unglycosylated FcγRIII 20 .…”
Section: Molecular Mechanisms To Account For the Enhanced Affinity Ofmentioning
confidence: 99%
See 2 more Smart Citations